Platelet-rich fibrin (PRF) graft and amniotic membrane graft on transforming growth factor-β (TGF-β) and type 1 collagen post conjunctival excision - Abdi Roy Nababan (Sanglah General Hospital, 2022)
Abstract Background: Conjunctiva, when injured, can heal spontaneously. However, in extensive wounds, wound healing is often accompanied by scarring and wound contraction. Currently, for cases of disease and trauma to the surface of the eyeball, it can be reconstructed using the amniotic membrane, but there are still weaknesses in the use of amnion. Platelet-rich fibrin (PRF) is currently being developed for the reconstruction of ocular surface wounds.